Trade with Mexico - Calof, Dan (Statistics Canada OttawaCA, 1991)
Defines in broad terms, how Canada-Mexico trade fits, in the context of total Mexican trade. Addresses the major underlying determinants of Mexico's trade, and recent Mexican trade policy initiatives.